ANALISIS KEBOCORAN SISTEM HIDROLIK PADA LANDING GEAR PESAWAT AIRBUS A330 SERIES MENGGUNAKAN METODE PDCA - Dwiaji, Yudhi Chandra; Sura, Anta (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2021)
The landing gear of the Airbus A330 aircraft uses a green hydraulic system, which is currently still found several leaks which result in a decrease in flight safety because the propulsion force on the landing gear does not function normally so it must use the freefall system when landing. This study analyzes the events that cause leaks of the flexible hose system, swivel valve and pitch trimmer. Flexible hose in Aircraft's Maintenance Manual has no limitations when a rapture occurs, while for swivel and pitch trimmers there are still limitations so that research is more directed towards the causes of leaks in flexible hoses. The hydraulic system leak data was taken in January 2020 – December 2020 with a total of 49 cases of leaking hydraulic system cases in the landing gear area, where flexible hose has a very high leakage rate compared to other cases. To identify the causes of hydraulic system leaks, this study uses ultrasonic internal leak measurement tools and hydraulic fluid analysis methods. Internal leak is used to determine hydraulic flow, while fluid analysis is to determine contamination of hydraulic fluid. In measuring the internal leak, the results are satisfied so that it is known that the flow rate is not the cause of the leak. While in fluid analysis measurements, from 10 registrations there were 5 registrations that obtained particle contamination results. Improvement progress using the PDCA method is expected to reduce the level of risk of leakage in the hydraulic system by making an engineering order (EO).